2015
DOI: 10.1021/acs.est.5b00208
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Injection of Microscale Zerovalent Iron Particles for Groundwater Remediation by Means of Complex Electrical Conductivity Imaging

Abstract: The injection of microscale zerovalent iron (mZVI) particles for groundwater remediation has received much interest in recent years. However, to date, monitoring of mZVI particle injection is based on chemical analysis of groundwater and soil samples and thus might be limited in its spatiotemporal resolution. To overcome this deficiency, in this study, we investigate the application of complex electrical conductivity imaging, a geophysical method, to monitor the high-pressure injection of mZVI in a field-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…These include investigations on biogeochemical transformations (FloresOrozco et al, 2011;Ntarlagiannis et al, 2005;Personna et al, 2008;Slater et al, 2007;Williams et al, 2005Williams et al, , 2009, oxidation-reduction (redox) reactions (Hubbard et al, 2014;Placencia-Gómez et al, 2013), mine tailings and acid mine drainage characterization (Campbell and Horton, 2001;Placencia-Gómez et al, 2015;Vanhala et al, 2005;Yuval and Oldenburg, 1996), monitoring of reactive iron barrier performance (Slater et al, , 2006Wu et al, 2005); and characterization of the polarization properties of different metal minerals (Abdel Aal et al, 2014;Gurin et al, 2013Gurin et al, , 2015Zhdanov et al, 2012) and nanoparticles (Joyce et al, 2012;Flores-Orozco et al, 2015). Such studies mainly focus on the role of the metal content (total weight or volume fraction percentage) and physical (textural) properties such as the metallic particle grain size and surface area on the spectral induced polarization (SIP) response.…”
Section: Introductionmentioning
confidence: 99%
“…These include investigations on biogeochemical transformations (FloresOrozco et al, 2011;Ntarlagiannis et al, 2005;Personna et al, 2008;Slater et al, 2007;Williams et al, 2005Williams et al, , 2009, oxidation-reduction (redox) reactions (Hubbard et al, 2014;Placencia-Gómez et al, 2013), mine tailings and acid mine drainage characterization (Campbell and Horton, 2001;Placencia-Gómez et al, 2015;Vanhala et al, 2005;Yuval and Oldenburg, 1996), monitoring of reactive iron barrier performance (Slater et al, , 2006Wu et al, 2005); and characterization of the polarization properties of different metal minerals (Abdel Aal et al, 2014;Gurin et al, 2013Gurin et al, , 2015Zhdanov et al, 2012) and nanoparticles (Joyce et al, 2012;Flores-Orozco et al, 2015). Such studies mainly focus on the role of the metal content (total weight or volume fraction percentage) and physical (textural) properties such as the metallic particle grain size and surface area on the spectral induced polarization (SIP) response.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a broad range of laboratory studies have been devoted in recent years to the assessment of reactivity (Freyria et al, 2011;Hosseini et al, 2011) and transport of iron particles in saturated porous media (Dalla Vecchia et al, 2009b;Freyria et al, 2011;Hosseini and Tosco, 2013;Tiraferri and Sethi, 2009;Tosco et al, 2014a), successful and well controlled pilot scale studies proving the feasibility of this approach are still limited, and mostly performed using nZVI (Bennett et al, 2010;Elliott and Zhang, 2003;Johnson et al, 2013;Macé et al, 2006;Mueller et al, 2012;O'Carroll et al, 2013;Quinn et al, 2005;Su et al, 2012), while mZVI field injection has been scarcely reported (Flores Orozco et al, 2015;Luna et al, 2013;Truex et al, 2011). The most critical issue in field scale applications of zerovalent iron particles is related to the generation of a wide and homogeneous reactive zone (Cameselle et al, 2013;Cook, 2009;EPA, 2003;Quinn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the IP response tends to increase with subsurface hydrocarbon concentration (Flores‐Orozco et al . ; Johansson et al . ) and this is often attributed to microbially mediated degradation of hydrocarbons.…”
Section: Microbially Mediated Processes and Applicationsmentioning
confidence: 99%
“…Non-polar (i.e. non-wetting) hydrocarbons tend to increase the IP signature of the subsurface (Revil, Schmutz and Batzle 2011;Flores-Orozco et al 2015;Johansson, Fiandaca and Dahlin 2015), while polar (i.e. wetting) ones have shown to either increase (Vanhala 1997;Kemna, Binley and Slater 2004;Deceuster and Kaufmann 2012) or dampen the IP effect (Ustra et al 2012;Personna et al 2013b).…”
Section: Hydrocarbon Degradationmentioning
confidence: 99%
See 1 more Smart Citation